Exploring the self-reported motivations of kratom (Mitragyna speciosa Korth.) use: a cross-sectional investigation. (4th July 2022) - Grundmann, Oliver; Veltri, Charles A.; Morcos, Diana; Knightes, David; Smith, Kirsten E.; Singh, Darshan; Corazza, Ornella; Cinosi, Eduardo; Martinotti, Giovanni; Walsh, Zach; Swogger, Marc T.
ABSTRACT: Background: Kratom ( Mitragyna speciosa Korth.) use outside of Southeast Asia has increased over the past decade. Objectives: This investigation clarifies kratom's role in perceived well-being, overall health, and temporal correlation with drug use to understand kratom's role in the self-treatment of substance use disorders (SUDs). Methods: Between July 2019 and July 2020 an anonymous, cross-sectional, online survey was taken by 7, 381 people who use kratom (PWUK) recruited through social media and other online resources. This included an assessment of (a) the relationship between self-reported overall health, concomitant use of drugs of misuse, and demographics; (b) the perceived effectiveness of kratom in self-treating diagnosed health conditions or symptoms; (c) the profile of PWUK primarily for drug dependence, pain, and mood or mental health conditions based on demographics. Results: A total of 5, 152 valid responses (45.9% females/53.7% males) were collected. Kratom was primarily used for self-treating pain (73.0%) and improving emotional or mental health conditions (42.2%) without clinical supervision. Those with a SUD (synthetic opioids, methadone, benzodiazepines, or heroin) used kratom after discontinuing illicit or other drugs (94.8%). The primary substances taken before or concomitantly with kratom were cannabis, cannabidiol, benzodiazepines, or kava. PWUKs report a dose-dependent benefit for alleviating pain and relieving negative moods. Adverse effects were primarily gastrointestinal, typically at high (>5 g/dose) and frequent (>22 doses/week) dosing. Conclusions: Kratom was primarily used as a harm-reduction agent for SUDs and self-treatment of chronic conditions. Healthcare professionals need better information about kratom, its potential adverse effects, and clinically significant drug interactions.